Перспективи використання європейського досвіду при впровадженні сучасної моделі децентралізації влади в Україні - Слободян, Богдан Юрійович; Slobodyan, Bohdan Yuriyovych (Ірпінь, 2024)
Робота полягає в аналізі європейського досвіду та підходів до впровадження оптимальної моделі децентралізації влади в Україні

The work consists in the analysis of European experience and approaches to the implementation of the optimal model of power decentralization in Ukraine
Prospects for using European experience in implementing a modern model of power decentralization in Ukraine
Keywords: публічна влада; децентралізація; модель децентралізації; децентралізаційні реформи; public power; decentralization; decentralization model; decentralization reforms